Pedunculopontine tegmental Nucleus-evoked prepulse inhibition of the blink reflex in Parkinson's disease. Issue 10 (October 2021) - Insola, Angelo; Mazzone, Paolo; Della Marca, Giacomo; Capozzo, Annamaria; Vitale, Flora; Scarnati, Eugenio
Highlights: Single stimuli applied to the pedunculopontine tegmental nucleus (PPTg) modulate the blink reflex (BR) in Parkinson's disease. The action of the PPTg on the BR differs from the action exerted by other basal ganglia nuclei. The PPTg has a critical role in the pathway mediating the prepulse inhibition of the BR. Abstract: Objective: To investigate the effects on the blink reflex (BR) of single stimuli applied to the pedunculopontine tegmental nucleus (PPTg). Methods: The BR was evoked by stimulating the supraorbital nerve (SON) in fifteen patients suffering from idiopathic Parkinson's disease (PD) who had electrodes monolaterally or bilaterally implanted in the PPTg for deep brain stimulation (DBS). Single stimuli were delivered to the PPTg through externalized electrode connection wires 3–4 days following PPTg implantation. Results: PPTg stimuli increased the latency and reduced duration, amplitude and area of the R2 component of the BR in comparison to the response recorded in the absence of PPTg stimulation. These effects were independent of the side of SON stimulation and were stable for interstimulus interval (ISI) between PPTg prepulse and SON stimulus from 0 to 110 ms. The PPTg-induced prepulse inhibition of the BR was bilaterally present in the brainstem. The R1 component was unaffected. Conclusions: The prepulse inhibition of the R2 component may be modulated by the PPTg. Significance: These findings suggest that abnormalities of BR occurring in PD may be ascribed to a reduction of basal ganglia-mediated inhibition of brainstem excitability.